Adherence to statin treatment following a myocardial infarction: an Italian population-based survey - Monaldi B; Bologna G; Costa GG; D'Agostino C; Ferrante F; Filice M; Grion A; Mingarelli A; Paloscia L; Tettamanti R; Veronesi C; Degli Esposti L (Dove Medical Press, 2015)
Bruno Monaldi,1 Giovanni Bologna,2 Geeta Giulia Costa,3 Carlo D'Agostino,4 Fulvio Ferrante,5 Maurizio Filice,6 Anna Maria Grion,7 Alessandra Mingarelli,8 Leonardo Paloscia,9 Roberto Tettamanti,10 Chiara Veronesi,11 Luca Degli Esposti11 1Servizio Farmaceutico, Ospedale G Mazzoni, ASUR Marche, Ascoli Piceno, 2Dipartimento Farmaceutico, Ospedale di Piacenza, AUSL di Piacenza, SSR Emilia-Romagna, Piacenza, 3Dipartimento Scienze Cardiologiche, Toraciche e Vascolari, Università degli Studi di Padova, Padua, 4Unità Operativa Cardiologia, Ospedale Di Venere, ASL di Bari, Bari, 5SC Monitoraggio Attività Farmaceutica, Azienda USL Frosinone, Frosinone, 6Dipartimento Medico, Ospedale Piero Palagi, Azienda Sanitaria di Firenze (ASF), Florence, 7Servizio Farmaceutico, ULSS 16 Padova, Padua, 8Dipartimento Funzionale del Farmaco, ASL di Latina, Latina, 9Unità Operativa UTIC e Cardiologia Interventistica, Ospedale Santo Spirito, ASL di Pescara, Pescara, 10Unità Operativa Complessa Osservatorio Epidemiologico e Sistemi Informativi, ASL della Provincia di Como, Como, 11CliCon Health, Economics and Outcomes Research, Ravenna, Italy Background: Statins are standard therapies after myocardial infarction (MI) in the general population. In the current study, we assessed adherence to statin treatment by patients after an MI in Italy, and estimated the effect of in-hospital statin therapy on persistence in treatment during a 2-year follow-up.Patients and methods: This was a retrospective cohort observation study of patients who experienced their MI between January 1, 2004 and December 31, 2005. Patients to enroll were identified by a diagnosis of MI at discharge from hospital. Previous drug therapies and hospital admissions for cardiovascular reasons in the 12 months before hospitalization for MI, statin treatment and lipid levels during hospitalization, indication for statin treatment at hospital discharge, and adherence to statin treatment in the following 24 months using an integrated analysis of administrative databases and hospital case records were evaluated. Also, factors associated either positively or negatively with consistent acute and long-term use of this efficacy-proven therapy were evaluated.Results: We identified 3,369 patients: 28.5% of patients had not been consistently treated with statins during their hospital stay for MI, and 36.2% of patients did not receive a statin prescription at hospital discharge. Of the 2,629 patients persistent with treatment during the follow-up, only 1,431 had an adherence to statins >80%. Either during the hospitalization or during the follow-up, the use of statins was negatively associated with older age and the presence of diabetes and chronic kidney disease. Lipid levels were significantly higher in treated than in untreated patients, but did not contribute to adherence to treatment. An important factor in long-term adherence to statin treatment was a statin prescription at the time of hospital discharge.Conclusion: Since the statin undertreatment rate in routine care is still high, physicians need to increase the awareness of patients regarding the implications of discontinuation and/or underuse of their medications and encourage higher adherence. Keywords: myocardial infarction, statins, adherence to treatment, discontinuation